(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study describes the clinical and paraclinical characteristics, management, and care of pregnant women with fetal distress during labor at Thai Binh Obstetrics and Gynecology Hospital in 2024. Research method: This prospective, cross-sectional descriptive study design surveyed 143 pregnant women diagnosed with fetal distress during labor at Thai Binh Obstetrics and Gynecology Hospital regarding clinical and paraclinical characteristics, obstetric management methods, and follow-up care for women with acute fetal distress during labor. Results: The average age of the mothers was 27.5 (88.1% under 35 years old), mainly primiparous women (67.8%). Meconium-contaminated amniotic fluid was the most typical symptom (87.4%). Premature rupture of membranes accounted for 62.9%; abnormal amniotic fluid volume accounted for 15.4%; 12.6% had rapid contractions; 14.0% had umbilical cord entanglement, and 3.5% had cerebrovascular index < 1; 21.7% of cases had abnormal fetal heart rate, with bradycardia being predominant (12.6%). Abnormal DIP and flat rhythms accounted for 7.7%. Cesarean section was the primary management method (90.2%); vaginal delivery and forceps delivery accounted for a low percentage (9.8%). 100% of pregnant women received comprehensive emergency care (oxygen therapy, fetal heart rate/contraction monitoring, psychological support, and preparation for neonatal resuscitation), were positioned on their left side (86.7%), and received glucose infusion (22.4%). Conclusion: The most common signs for early diagnosis of fetal distress during labor are meconium-stained amniotic fluid and abnormal fetal heart rate on the monitoring. A combination of comprehensive intensive care and timely obstetric management is necessary to ensure a safe obstetric outcome.